Dugo putovanje kroz istoriju, historiju i povijest . The Long Road Through Balkan History - Markovic, Željko (SEETV, 2010)
Verzio FF The film explores different visions of the common past in the Balkans and how those differing visions impact the present and the future of the region. The film is a journey through the past, present and future, from Slovenia to Macedonia, via Croatia, Bosnia and Serbia. The main protagonists are two writers, Miljenko Jergović from Croatia and Marko Vidojković from Serbia. They share the driving in a Yugo car, the ultimate symbol of their common past, and drive it from one end to the other of the road once known as the "Highway of Brotherhood and Unity." They aim to look at their common past, find out how history has set them apart, ask where the present is leading them — and have a lot of fun while they are about it. As the Yugo dodges lorries, fast cars and queues at endless border checks, they take a wry look at the state of the Balkans. They sing along to nostalgic Yugoslav favorites, comment on the radio news and above all stop to ask those who can tell them how they got there and where the highway of history is taking them next.